1988
DOI: 10.1007/bf00163539
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of patients with short and long survivals after detection of intracranial metastases from breast cancer

Abstract: The clinical course of 106 patients with brain metastases from breast cancer was retrospectively studied. Median time of survival after detection of intracranial metastases (SAR(ICM] was 14 weeks (95% confidence limits: 10-19 weeks), and 25% of the patients survived for more than 37 weeks, while only 17% survived for one year. The occurrence of clinical, pathoanatomical and therapeutical variables in these patients were analyzed in a subgroup of 57 patients, who survived for less than 16 weeks, and compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
5
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 19 publications
3
5
0
Order By: Relevance
“…The median age of 50 years in our patient population is consistent with previous studies of patients with breast cancer with brain metastases, in which the median age was 51 years (1,13). In addition, the high proportion of brain metastases presenting as the first site of distant disease, 29% in our study, is consistent with data reported in the literature (13,15,33). Paterson et al suggested that this unusually high rate of brain metastasis as the initial site of distant disease is related to the aggressive systemic therapy initiated at the time of the primary diagnosis (33).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The median age of 50 years in our patient population is consistent with previous studies of patients with breast cancer with brain metastases, in which the median age was 51 years (1,13). In addition, the high proportion of brain metastases presenting as the first site of distant disease, 29% in our study, is consistent with data reported in the literature (13,15,33). Paterson et al suggested that this unusually high rate of brain metastasis as the initial site of distant disease is related to the aggressive systemic therapy initiated at the time of the primary diagnosis (33).…”
Section: Discussionsupporting
confidence: 94%
“…The majority of the literature regarding RT describes the use of WBRT. Data regarding the use of WBRT consistently shows a median survival range for patients with breast cancer with brain metastases to be 12 to 16 weeks (1,6,12,15,16). Regarding stereotactic radiosurgery, there are currently no significant data with regard to its success in managing brain metastases in patients with breast cancer (7).…”
mentioning
confidence: 97%
“…These results are similar to most of the published data and confirm that in breast cancer patients with signs and symptoms of neurological disease the diagnostic approach should associate neuroimaging with CSF examination 3,12,18 . The introduction of CEA and CA-15.3 analysis in the CSF work-up showed promising results, particularly as a diagnostic aid in leptomeningeal neoplasms.…”
Section: Discussionsupporting
confidence: 90%
“…Recent epidemiological data indicate that the incidence of CNS metastasis has been increasing in the last two decades; this could be explained by the increased survival of the breast cancer patients nowadays 3,4 . The clinical presentation of these patients is pleomorphic, depending on the localization of the lesions, meningeal involvement and paraneoplastic syndromes, as well as on therapeutic complications 2,5 .…”
mentioning
confidence: 99%
“…Whole brain radiation alone has been reported to be associated with a 3-to 4-month survival in these patients. 1,[11][12][13][14] Chemotherapy is not widely used to treat metastases to the brain. A small number of available reports, however, cite an approximate 7-to 8-month survival in this population.…”
Section: Discussionmentioning
confidence: 99%